Isopleths for Rainfall Data in Sabah - Kurian, V.J.; Febik, J.K.; Nurmin, B.; Ideris, Z. (American Society of civil Engineers, 2006)
Isopleths are lines along which rainfalls have the same specified intensity. These isopleths form the basic information needed for the design of systems needed for roof drainage, urban drainage, water supply, irrigation and flood control. Hence they are very important for 'water management'.